Minorities, Minority Rights and Internal Self-Determination - Barten, Ulrike (Springer, 2015)
The book questions the classic idea of self-determination – the right to self-determination is a right of peoples, not of minorities – by examining the content of the right to self-determination and the content of minority rights. Self-determination has four dimensions: the political, the economic, the social and the cultural dimensions. Minorities have minority rights that touch on most aspects of life as a member of a minority. If there is an overlap between minority rights and the different dimensions of self-determination, the concept that the right to self-determination is only applicable to peoples loses credibility. No global and general conclusion is envisaged; there are restrictions in place. The work is limited to the European framework and is further restricted to classic minorities. The argument is based on a legitimacy and justice approach. The analysis in this book shows that some minority rights overlap with the different dimensions of internal self-determination. In short, classic minorities in Europe have a right to internal self-determination.